Correlation between Fatty Acid Transport Proteins and Phosphoinositide 3-Kinase Pathway in Breast Cancer - Acharya, Ranjitha; Nalilu, Suchetha Kumari; Shetty, Shilpa Sharathraj; Shetty, Abhijith Sudhakar; Monteiro, Flama; Ganeshkodi, Roopashree Padmanabha (Biomedical and Biotechnology Research Journal, 2024)
Abstract Background: Breast cancer (BC) is currently the fifth largest cause of mortality worldwide and has become the most frequent type of cancer. Fatty acid transport proteins (FATPs) assist cancer cells in meeting their higher metabolic needs by increasing fatty acid uptake, which is a significant source of energy for cancer cells. The phosphoinositide 3-kinase/protein kinase B/mammalian target of the rapamycin (PI3K/Akt/mTOR) pathway is an important signaling pathway that coordinates the uptake and utilization of various nutrients, including fatty acids. The current study aimed to correlate the FATPs with the PI3K/Akt/mTOR pathway in BC. Methods: Eighty serum samples were collected from BC and control subjects after obtaining an informed consent form. Total ribonucleic acid (RNA) was isolated, and the relative messenger RNA (mRNA) expression of PI3K, Akt, and mTOR was analyzed by a reverse transcriptase-quantitative polymerase chain reaction. Serum FATPs were estimated using commercially available enzyme-linked immunoassay kits. P < 0.05 was indicated as statistically significant. Results: The serum FATPs in subjects with BC differed significantly compared to the control. Relative mRNA expression of PI3K, Akt, and mTOR differed significantly between the groups. Further, on correlating the serum FATPs with PI3K-related signaling molecules showed a significant positive correlation within BC subjects. Conclusion: Significant positive correlation between FATPs and the PI3K, Akt, and mTOR pathway suggests a crucial role of FATPs in promoting BC.